Fabrication of continuous electrospun filaments with potential for use as medical fibres. (19th May 2015) - Mouthuy, Pierre-Alexis; Zargar, Nasim; Hakimi, Osnat; Lostis, Emilie; Carr, Andrew
Abstract: Soft tissue injuries represent a substantial and growing social and economic burden. Medical fibres are commonly used to repair these injuries during surgery. Patient's outcomes are, however, not promising with around 40% of surgical repairs failing within the first few months after surgery due to poor tissue regeneration. The application of nanofibrous filaments and yarns as medical fibres and scaffolds has been suggested to improve soft tissue regeneration and enhance the quality of the repair. However, due to a lack of robustness and reliability of the current fabrication methods, continuous nanofibrous filaments cannot be manufactured and scaled up in industrial settings and are not currently available for clinical use. We have developed a robust and automated method that enables the manufacture of continuous electrospun filaments and which has the potential to be integrated into existing textile production lines. The technology uses a wire guide to form submicrofibres in a dense, narrow mesh which can be detached as a long and continuous thread. The thread can then be stretched and used to create multifilament yarns which can imitate the hierarchical architecture of tissues such as tendons and ligaments. Electrospun polydioxanone yarns produced by this method showed improved cellular proliferation and adhesion when compared to medical monofilament fibres in current clinical use. In vivo, the electrospun yarns showed a good safety profile with mild foreign body reaction and complete degradation within 5 months after implantation. These results suggest that this filament collection method has the potential to become a useful platform for the fabrication of future medical textiles.